Causes of Absenteeism from the Schools at Secondary Level - Shahzada, Gulap; Ghazi, Safdar Rehman; Nawaz, Habib; Khan, AbdUllah (Mediterranean Journal of Social Sciences, 2011)
The study aimed at to find out different causes of students’ absenteeism at secondary level in district Bannu, to sort out social,political and economic factors involved in the students’ absenteeism at secondary level. All secondary level students’ of district Bannuconstituted population of the study.100 students who frequently remained absent from the schools were conveniently selected as a sample ofthe study. Percentages have been used as statistical technique to analyze the data. Results of the study showed that most frequent causes ofthe absence of the students from the schools were their families’ participation in social activities, students help their parents in their work,too much home work and too many tests and examinations. It was recommended that by the care and concentration of parents, childrencan be encouraged to go to school. Availability of the school building, furniture, adequate libraries and clean and healthy environment,introducing modern methods and techniques, keeping in view the interests and needs of the children, providing financial aid to the studentswho are unable to afford the educational expenses, teachers’ sympathetic attitude are factors which can motivate and attract studentstowards schools.